Effectiveness of the “Intip Aja Kalau Gak Percaya” Application in Improving Adolescents’ Knowledge about Premarital and Preconception Health - Awatiszahro, Alfika; Betanuari Sabda Nirwana; Qotrunnada Aidatil Fitriya (Universitas STRADA Indonesia, 2025)
Adolescence is a critical developmental period characterized by rapid physical and psychosocial changes that influence reproductive health behaviors. Limited knowledge about premarital and preconception health contributes to risky behaviors such as early marriage, unplanned pregnancy, and inadequate preparedness for future reproductive roles. Digital media provides an accessible platform for health education among adolescents. To evaluate the effectiveness of the “Intip Aja Kalau Gak Percaya” (Information and Tips for Teenagers to Prevent Premature Marriage and Pregnancy) application in improving adolescents’ knowledge regarding premarital and preconception health.